STRUCTURAL STUDY OF CARBOXYLATE LIGAND COMPLEXES - MARTAK (NIM: 30504007), FAHIMAH
Carboxylate complexes of first row transition metals have been structurally and extensively studied due to their tendency to form open network structure such that they can be utilized as hydrogen storage material. In addition, the carboxylate group of the complexes can bridge various metal ions to form porous structure that may function as adsorban as well as catalyst. Carboxylate complexes have been studied several decades, however, in the last ten years a number of studies has expanded the complexes by employing synthesis using varied reactants and synthesis conditions. In this research, the structure of carboxcylate complexes with picolinic and oxalate as ligands were studied. Picolinic framework was chosen as ligand because it has a pyridine ring and carboxylate group that result in electrons resonance. Moreover, the coordination modes of picolinic ligand with metals are widely varied, hence structural studies need to be done. Seven single crystals of picolinic complexes of first row transition metals with two and three oxidation states have been synthesized and their structures have been determined using single crystal X-ray diffraction. The obtained picolinic complexes could be classified into two classes: (1) complexes that form one dimensional chains; (2) complexes that form two dimensional chains. One dimensional complex is resulted from the synthesis are Mn(III), Fe(III) and Co(III) cations each coordinated with three picolinic ligands and the existence of hydrating water molecules. These water molecules formed hydrogen bond between picolinic complexes that result in one dimensional framework. One dimensional complex was obtained also from the compound containing of Cu(II) cations coordinated with two picolinic ligand and the existence of two hydrated water molecules. Two hydrated water molecules form intramolecular O-H-H hydrogen bond, so results in dimmer molecule. The dimer of water molecule links the bis(pic)-Cu(II) chains forming an infinite one-dimensional structure. Two dimensional complex was obtained in the compound containing of Fe(II) and Ni(II) cations equatorially coordinated with two picolinic ligands and axially coordinated with two water molecules, and the existence of hydrated water molecules. In addition to two water molecules acting as ligands, there were also two hydrated water molecules. The hydrated water in the bis(pic)di(aqua) -nickel(II) and -iron(II) complexes formed hydrogen bond in two direction that resulted in the formation two dimensional framework of the complexes. In the first direction, one hydrogen atom of coordinated water is hydrogen bonded to carboxylate oxygen atom which is coordinated to the metal ion. The other hydrogen atom of the same coordinated water molecule is hydrogen bonded to oxygen atom of hydrated water. In the second direction, oxygen atom of carboxylate which is not coordinated to the metal ion is hydrogen bonded to the hydrogen of hydrated water. The tris(pic)-M(III) complexes with M(III) represents the transition metals of Mn, Fe, and Co showed that all picolinic acid ligands underwent deprotonation, so they act as anionic ligands. This resulted in the formation of neutral complexes. Picolinic ligands coordinated to metal atoms acted as bidentate ligand through N and O donor atoms forming five-membered ring. Metal ions coordinated to the ligands resulted in slightly distorted from ideal octahedral structure. The relative disposition of the nitrogen and oxygen atoms shows that [Mn(pic)3] complex has the meridional stereochemistry. The novel result of this research is the isolation of tris(pic)-Mn(III) complex, the metal ion in this complex has d4 electron configuration which is usually unstable and hard to be synthesized. In these complexes, tris(pic)-iron(III) has the longest average Fe-N distance, and it is also observed for the average Fe-O distance. The complex that binds three picolinic was also obtained from iron(II) metal ion, but picolinic ligan was resulted from hydrolysis of the 1,2-bis(2-piridil)etandion ligand. The crystal structure of this complex was different from that of picolinic complexes described above because it forms a single charge cationic complex. This study also gave information that the complex formed dimer structure. This dimer structure was formed by a hydrogen bond. An iron(II) metal ion coordinated to three deprotonated picolinic ligands and the other iron(II) metal ion coordinated to three picolinic acid ligands. This cationic complex was counteracted by one tetrafluoroborate anion. The second class were bis(pic)-M(II) compounds where M(II) were iron, nickel and copper. Structural studies on the iron(II) and nickel(II) compounds showed two picolinic ligands in equatorial plane and two water molecules coordinated to metal ion with trans geometry. The formation of complexes with trans coordinated ligand is very important because it can be used as precursor to obtain polynuclear complexes. This polynuclear complex can be obtained by substituting H2O ligand in trans position with other bridging ligand. From bis(pic) complexes with copper(II), metal ion coordinated to oxygen and nitrogen atoms of two picolinic ligands in the equatorial plane and also weakly coordinated to two intramolecule carboxylate group in the axial plane. In this research, carboxylate complexes containing oxalate ligands were also synthesized. Oxalate ligand can connect metal ions to form anionic polynuclear complexes. The anionic complex formed cavities, which was filled by organic cation. Usually the organic cation consists of tetra alkyl molecule. The use of organic cation tetrabutyl phosphine in this research instead of tetrabutyl amine was aimed to obtain bigger cavities. This strategy was conducted as template that can be substituted by other cationic complex. Complexes which were synthesized with oxalate ligand were a single charge anionic binuclear complex. All oxalate complexes have formula [P(nC4H9)4][MCr(ox)3] with M = Mn, Fe, Co, Ni and Cu. Structural determination of polycrystal binuclear oxalate complexes were carried out using X-ray diffraction and Le Bail method in Rietica program. All the oxalate complexes showed that all the compounds have similar structure. The structure of this complex was composed of two dimensional bimetallic [MCr(ox)3]- anionic network. This network is composed of bis-bidentate oxalate ligand connecting M(II) and Cr(III) ions in such away that each M(II) ion and Cr ion is surrounded by three alternating oxalate ligand, leading to polymeric nets. This network forming cavities was filled by the counter ion tetrabutyl phosphine [P(nC4H9)4]+. The five complexes show the existence of ferromagnetic interaction between Cr(III) and M(II) ions: the increase of susceptibility magnetic at low temperature, saturation magnetization and magnetic hysterisis loops at 5 K. The TCW values for five dinuclear oxalate compounds are given respectively 15,13 (MnCr), 12,64 (FeCr), 11,58 (CoCr), 10,83 (NiCr) dan 9,85 K (CuCr). The decreasing value trend is caused by the decreasing of the magnetic interactions between metal ions.